Analysis Of Declining Air Production Pressurized On The Compressor On Board The MV. Uniorder - Miran, Miran; Tungkup, Doharman Lumban (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Compressor has the most important on the ship, in support the operational of ship. In it is the oprational compressor often experience influence that cause low of the pressure air production of compressor on ship, till the writer is interestid to create it in skirtion with title the low analysis of pressure air production of compressor. This research conducted when writer to execute practice of sea (sea object) for MV.UNIORDER property of company PT. Asia Mulia Transpasifik for 1 year. Data source obtained directly from place of research with observation method as well as biography method in the form of documents, instruction manual book and books related to title of this research. The result of this observation is the slags on the valve and seratchs of the surface valve which cause decrease low of pressure air production of compressor, till causes the main engine could not started. The suggest of writer in this research is clean the compressor every day in order the our that is absorbed not content any carbon and dush. Attending also the maintenance of every valve. Both the suction valve although pressure valve and attention also the running hours from compressor valve.